Comparison of Defection Frequency in Infant Age 0 to 4 Month between Breast Milk And Formula Milk in Toddopuli Public Health Center - St Hadijah H Anwar; Rosdianah Rosdianah; Abd Rahman Abd Rahman (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Breast Milk is an emulsion of fat in a solution of protein, lactose, and inorganic salts secreted by the mother’s mammary gland. Formula milk is cow’s milk whose nutritional composition is changed in such a way that it can be given to babies without giving side effects, cow’s milk itself is a milk of choice for babies who have no family history of allergies. Defecation is the act of a living for or the process of a creature removing solid or half-solid feces or stool originating from the digestive system of living things. This study aims to determine the comparison of the frequency of defecation in infants aged 0-4 months between breast milk and formula milk in the work area Makassar toddopuli health center in 2019. This study uses the Cross-Sectional Study approach which is the type of research in the form of Observation of independent and dependent variables conducted at the same time. Purposive sampling technique. The respondents of this study were 30 people. The observation was carried out for 4 months by recording the expenditure of the baby’s chapters every day. Because the data is not normally distributed, the Tann Pitney statistical test was used and a p-value of 0,000 (p0.05) was obtained. So it can be concluded that the results of this study are that there is a comparison of the frequency of defecation in infants aged 0-4 months between breast milk and formula milk in Makassar toddopuli health center in 2019.